Visualization, modelling and analyzing of transport space in cities from the aspect of aesthetics evaluation - Żakowska, Lidia (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Author claims that protection of transport space environment covers all actions which enhance aesthetics of this space and which upgrades its visual properties. Protection of transport environment which is realized in a constant care of visual effect, creates a new approach to transport sustainable development research. The considerations on aesthetical evaluation in transportation are presented based on visualization methods, first at classical two-dimensional approach of linear perspective and finally in form of four-dimensional intelligent digital models of virtual space. Transport environment visualization characteristics and their perception in relation to aesthetic properties are studied, also the new emerging science of visualization is described, and finally the future directions of visualization in urban transportation development are predicted.